DZIAŁALNOŚĆ GOSPODARCZA ORGANIZACJI POŻYTKU PUBLICZNEGO - Trzaskowski, Roman (Zeszyty Prawnicze, 2017)
Commercial Activity of Nonprofit Organizations Summary The issue of the economic activity of nonprofit organizations is highly controversial in Poland. Some scholars argue that this sort o f activity should not be opened for the third sector organizations at all because in practice it often dom inates over the statutory activity, constitutes the fields of abuses and casts shadow on the good reputation of the sector. The others believe that the non governmental organizations should have the possibility to engage in business activities subject to certain conditions. The second position has been accepted by the Polish legislator in the recent law on the public utility activity and voluntarism from June 23th, 2003. The law provides for a relatively detailed and interesting regulation of the economic activity of so called public utility organizations, that is the organizations which - because of their public utility character - are treated in a very favorable manner by the legislator (e.g. from the perspective of tax law). The legislator distinguishes between business activity, paid and free public utility activity (art. 6-10). The difference between a business activity and a paid public utility activity depends on the level of the fee charged for the goods or services. If the fee is not intended to generate net income but only to cover the direct costs of the goods or services provided by the organization, then in principle it is „a paid public utility activity”. This activity may constitute the statutory activity of a public utility organization. However the legislator has also decided, that „a paid public utility activity” constitutes a business activity in a case where the payment of the natural persons employed by the organization exceeds 150% of the average payment. As to the business activity, the legislator has decided that the business activity of the public utility organization has to serve its statutory goals (art. 20 p. 4). It means that this activity may only have a subsidiary character and may not constitute a main statutory activity of the organization.